BIRTH WEIGHT, WEIGHT GAIN, AND OBESITY AMONG CHILDREN IN URUGUAY: A PROSPECTIVE STUDY SINCE BIRTH - Pereyra,Isabel (2021)
ABSTRACT Objective: To examine the effect of birth weight and subsequent weight gain on children being overweight and obese in serial assessments of Uruguayan children living at urban areas. Methods: We used secondary data of pediatric anthropometric measurements and health and socioeconomic characteristics of families that were included in a longitudinal and prospective nationally representative survey (“Encuesta de Nutrición, Desarrollo Infantil y Salud”). The associations of conditional weight gain, being overweight and obesity were tested through correlation coefficients. Multivariate binary logistic regression models were performed to calculate the effect of birth weight on childhood obesity and were adjusted for covariates. Results: For macrosomic babies, there was an increase in the prevalence of overweight and obesity in 70% compared with non-macrosomic babies, when we adjusted for sex, exclusive breastfeeding duration, and household income. The correlation between weight gain and the body mass index for age indicated that the greatest (positive) difference in Z score between measurements increased the obesity levels. Conclusions: Our findings suggest that ensuring optimal birth weight and monitoring and controlling posterior weight gain represent the first steps toward primary prevention of childhood obesity.